Madhyapradésa ke jilevāra ārthika sūcakāṅka, 1960-61 se 1974-75 (Ārthika Viśleshaṇa Sambhāga, Ārthika evaṃ sāṅkhyikī Sāncālanālaya, Madhyapradēśa, 1978)
Economic indicators of Madhya Pradesh by district.